POLITIK KRIMINAL OPTIMALISASI PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA REVENGE PORN - Veronica Agustina Darida (Prodi Ilmu Hukum Fakultas Hukum Universitas Warmadewa, 2024)
Revenge porn is on the rise, and many minors are victims. Revenge porn is a criminal act of pornography with the motive of revenge for the perpetrator against the victim by disseminating immoral content on social media. Optimizing legal protection for children who are victims of revenge porn is very necessary considering that children are weak individuals, and the negative impacts they cause will greatly disrupt their physical health, such as feeling tired and muscle tension due to excessive anxiety, as well as psychological disorders in children which can cause excessive stress and severe trauma. Revenge porn for children will disrupt the child's continued life. This research aims to examine legal protection for children as victims of revenge porn in statutory regulations, especially the TPKS Law. This research is normative research which is studied using a statutory approach and a conceptual approach. The results of this research show that there are several challenges in the provisions of the TPKS Law which could become obstacles to implementing legal protection for victims of revenge porn. The implementation of criminal politics is needed to optimize legal protection for revenge porn victims, especially children. Criminal politics consists of penal policies and non-penal policies. By implementing every legal provision that regulates revenge porn, accompanied by the implementation of criminal politics, this is a form of preventing the occurrence of revenge porn, and as a form of optimizing legal protection for victims of revenge porn, especially minors.